Taśawwurât al-Jâihah fî Riwâyât al-Ĥayâli al-‘Ilmî (Depiction of Pandemic in Science Fiction Novels) - Noora TC; Sabique MK (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2022)
جائحة كورونا أجبرنا على إعادة فحص تراثنا الأدبي من أجل البحث عن الحلول أو طرق للتصدي وكيفية التعامل مع الوباء. حاولت الباحثة في هذه الدراسة رصد معالجات أدب الخيال العلمي الشعبي والفني لظاهرة الجوائح التي سبقت جائحة كورونا، والتي توقعت حدوث مثل هذه الجائحة، وكذا توضيح تصورات هذا النوع من الأدب تجاه الفيروسات بشقيها الإلكترونية كفيروسات الحواسيب والمرضية كفيروس كورونا أو الإنفلونزا أو غيرها. وجد البحث قد شهد العالم عديد من الأوبئة مختلفة الأجناس طوال العصور. حقا فقدنا الكثير من الأرواح، على الرغم الخوف من الجائحات في البداية، تغلب البشر على كلها وكتبنا تاريخ البقاء. مع أن الأدبيات تظهر التقنيات مثل الإبعاد الاجتماعي، والكمام، الحجز الصحي والإغلاق التام، وأن جميع الكتب والروايات تشترك معظم الروايات في روح الإيجابية. الشجاعة والرجاء والدعاء والأهم أنها تزيد الإيمان بالله. The Corona pandemic has forced us to re-examine our literary heritage in order to search for solutions or ways to address and how to deal with the epidemic. In this study, the researcher tried to monitor the treatments of popular and artistic science fiction literature on the phenomenon of the pandemics that preceded the Corona pandemic, which expected the occurrence of such a pandemic, as well as clarifying the perceptions of this type of literature towards viruses, in their electronic parts, such as computer viruses and diseases such as the Corona virus or influenza or others. The research found that the world has witnessed many epidemics of different races throughout the ages. Indeed, many lives have been lost, despite the fear of pandemics in the beginning, humans have overcome all and we have written a history of survival. Although the literature shows techniques such as social distancing, gag, quarantine and total closure, and all books and novels share most of the novels in the spirit of positivity. Courage, hope and supplication, and most importantly, increase faith in God.